Repercussion of biofilm and antibiotic resistance in ventilator associated pneumonia - S., Vinodkumar C.; Patil, Satish S.; A., Arun Kumar; Prasad, B. S.; Kalappanavar, N. K.; K., Niranjan; K. R., Shama Taj; K. G., Raghu Kumar; L., Jayasimha V.; G., Basavarajappa K. (International Journal of Research in Medical Sciences, 2017)
Background: Ventilator associated pneumonia contributes nearly half of all cases of hospital-acquired pneumonia. Drug resistance among ventilator associated pneumonia has obligation of device withdrawal in order to achieve clinical and microbiological cure. Aim of the study was to determine the relationship between antibiotic resistance of Endotracheal tube biofilm and pulmonary pathogens in ventilator-associated pneumonia. Methods: A descriptive analytical study of 100 clinically suspected VAP patients was done. Patients were divided into group-I and Group-II based on intubation duration for 1-5 days and 6-10 days respectively. Endotracheal aspirate (ETA) was collected from clinically diagnosed cases and processed as per standard microbiological techniques. Bacterial counts ≥106 CFU/ml for quantitative cultures was considered significant. Biofilm production was detected by tissue culture plate, tube method and Congo red method. Multi-variant analysis was done to find out the association of the various factors. Results: Klebsiella pneumoniae was the predominant bacteria isolated followed by Acinetobacter baumannii. 45% of Gram negative bacteria were β lactamase producers. In Biofilm production by tissue culture method, 72% of the isolates showed either strong or moderate biofilm formation. Multivariate analysis revealed that bacteria isolated from VAP occurring after 5 days of mechanical ventilation among prior antibiotic-treated patients were resistant to all the antibiotics tested. Conclusions: Bacterial aetiology, biofilm formation and drug resistance has ramification on outcome of ventilator associated pneumonia. Hence, advised that it is crucial to remove ET tube in regular interval to prevent biofilm formation and sequential cultures to obtain the microbiological information which enables better patient care.